HUBUNGAN KARAKTERISTIK DENGAN PHBS DI SMA NEGERI 1 PANCUR BATU - Pomarida Simbolon (STIKes Santa Elisabeth Medan, 2018)
Schools as one of the centers of education for the children of the nation, up to now have not been able to carry out recommendations to be able to behave clean and healthy. If PHBS is not done well, it will cause undesirable effects, namely the emergence of various diseases and poor health status. This was found in 1 Pancur Batu Public High School in Deli Serdang District. Goals : The purpose of the study was to determine the relationship of characteristics with PHBS in-state high schools 1 Pancur Batu. Methods: This type of research is cross-sectional conducted at 1 Pancur Batu Public High School. The sample in the study amounted to 88 people with a simple random sampling technique. Data collection using a questionnaire. Data were analyzed using the chi-square test. Results: The results showed that there was a sex relationship (p = 0.007, class level (p = 0.001) with PHBS. Conclusion: It was suggested that the 1 Pancur Batu Public High School be advised to collaborate with Pancur Batu Health Center to create a schedule for providing health education so that knowledge of school children more updates about PHBS.